TERTOLAK TETAPI MENJADI BERKAT BERDASARKAN KITAB HAKIM-HAKIM 11:1-11 - Kori Parina; Hendrianto ST., M.A (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2021)
Jephthah experienced rejection in the Gilead family, he was expelled from the Gilead family because Jephthah did not have the right to inherit Gilead's property. The Israelites at Mizpah were oppressed by the Ammonites for 18 years and according to God's will, Jephthah was chosen to be the liberator of the Israelites from oppression and he became the judge of the Israelites for six years. from the Jephthah character who also experienced rejection in the Gilead family and even his own tribe because he was not a legitimate child from Gilead which caused him to be expelled and at the end of his life he was elected as a judge over the Israelites to free the Israelites from oppression, this is what the author makes motivation to everyone who has experienced rejection to be able to bring change with the potential that exists within. The method used by the author is descriptive qualitative and also descriptive quantitative, because in addition to using literature and supporting journals, the author also conducts field observations using questionnaires from respondents as valid data and the authors can be held accountable.From studying the character of Jephthah from the book of Judges 11:1-11 that God has potential for everyone, rejection is not the end of everything, to be a blessing there needs to be healing from within the person, recovery can only be obtained in a relationship with God . The motivation that can be given to people who experience rejection is to awaken the potential that exists within themselves, self-acceptance is the beginning to experience change, to be a blessing to anyone, to be a person who wants to humblethemselves. From this study the authors obtained the results that do not make rejection as a benchmark so that it hinders self-potential to step up and bring change for the better.Jephthah experienced rejection in the Gilead family, he was expelled from the Gilead family because Jephthah did not have the right to inherit Gilead's property. The Israelites at Mizpah were oppressed by the Ammonites for 18 years and according to God's will, Jephthah was chosen to be the liberator of the Israelites from oppression and he became the judge of the Israelites for six years. from the Jephthah character who also experienced rejection in the Gilead family and even his own tribe because he was not a legitimate child from Gilead which caused him to be expelled and at the end of his life he was elected as a judge over the Israelites to free the Israelites from oppression, this is what the author makes motivation to everyone who has experienced rejection to be able to bring change with the potential that exists within. The method used by the author is descriptive qualitative and also descriptive quantitative, because in addition to using literature and supporting journals, the author also conducts field observations using questionnaires from respondents as valid data and the authors can be held accountable.From studying the character of Jephthah from the book of Judges 11:1-11 that God has potential for everyone, rejection is not the end of everything, to be a blessing there needs to be healing from within the person, recovery can only be obtained in a relationship with God . The motivation that can be given to people who experience rejection is to awaken the potential that exists within themselves, self-acceptance is the beginning to experience change, to be a blessing to anyone, to be a person who wants to humblethemselves. From this study the authors obtained the results that do not make rejection as a benchmark so that it hinders self-potential to step up and bring change for the better.